2012
DOI: 10.5402/2012/706937
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Cardiac Dysfunction in Children with Coeliac Disease: Is the Gluten-Free Diet Effective?

Abstract: Objectives. The aim of this study is to investigate the effects of coeliac disease on cardiac function in children using conventional transthoracic echocardiography (TTE) and tissue Doppler echocardiography (TDE). Methods. Coeliac disease patients were evaluated in two different groups based on serum endomysial antibody (EmA) titers (EmA (+) and EmA (−)), and the data obtained by conventional and TDE studies were compared between the patient groups and healthy controls. Results. There was no significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
(32 reference statements)
2
16
0
Order By: Relevance
“…Due to obtained data regarding cardiac involvement in patients with CD, recent studies focused on noninvasive echocardiographic methods which can detect subclinical carditis before development of potential dilated cardiomyopathy . A few studies have indicated that early cardiac involvement in patients with CD can be detected by TDI echocardiography in both adults and children . In our study, none of the patients with CD had LV systolic and diastolic dysfunctions according to conventional echocardiography.…”
Section: Discussionmentioning
confidence: 42%
“…Due to obtained data regarding cardiac involvement in patients with CD, recent studies focused on noninvasive echocardiographic methods which can detect subclinical carditis before development of potential dilated cardiomyopathy . A few studies have indicated that early cardiac involvement in patients with CD can be detected by TDI echocardiography in both adults and children . In our study, none of the patients with CD had LV systolic and diastolic dysfunctions according to conventional echocardiography.…”
Section: Discussionmentioning
confidence: 42%
“…Saylan et al . [23] reported no significant difference between CD children and healthy controls regarding the ejection fraction and FS parameters, however, the interventricularseptal systolic dimension (IVSD) and LV end diastolic diameter (LVEDD) parameters were significantly different between EMA (+) and EMA (−) groups as well as the control group. Lionetti et al .,[24] in a study among 40 children with CD, using two-dimensional and M-mode echocardiography detected mild cardiac affection in 9 out of 40 patients in the form of mitral valve regurgitation (5 patients), aortic valve regurgitation (2 patients), pulmonary and tricuspid valve regurgitation (1 patient), and low ejection fraction (1 patient).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Saylan et al . [23] reported a significant difference in DTI parameters including mitral valve early diastolic (Em) velocity, mitral valve late diastolic (Am) velocity, mitral Em/Am ratio, tricuspid valve early diastolic (Em) velocity, and LV myocardial performance index between CD patients and the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Cevik et al 3 reported that, the TDE parameters of LV myocardial performance index (MPI) and LV IVRT were effective in patients with CD.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, cardiovascular system pathologies such as myocarditis and idiopathic dilated cardiomyopathy (IDCM) have also been found to be associated with CD 2 . These studies about CD suggest that subclinical involvement of cardiovascular system is much more frequent than IDCM and myocarditis 3,4 .…”
mentioning
confidence: 99%